Mitochondrial-dependent apoptosis in Huntington's disease human cybrids - Ferreira, IL (2010)
We investigated the involvement of mitochondrial-dependent apoptosis in Huntington's disease (HD) vs. control (CTR) cybrids, obtained from the fusion of human platelets with mitochondrial DNA-depleted NT2 cells, and further exposed to 3-nitropropionic acid (3-NP) or staurosporine (STS). Untreated HD cybrids did not exhibit significant modifications in the activity of mitochondrial respiratory chain complexes I-IV or in mtDNA sequence variations suggestive of a primary role in mitochondrial susceptibility in the subpopulation of HD carriers studied. However, a slight decrease in mitochondrial membrane potential and increased formation of intracellular hydroperoxides was observed in HD cybrids under basal conditions. Furthermore, apoptotic nuclei morphology and a moderate increase in caspase-3 activation, as well as increased levels of superoxide ions and hydroperoxides were observed in HD cybrids upon 3-NP or STS treatment. 3-NP-evoked apoptosis in HD cybrids involved cytochrome c and AIF release from mitochondria, which was associated with mitochondrial Bax translocation. CTR cybrids subjected to 3-NP showed increased mitochondrial Bax and Bim levels and the release of AIF, but not cytochrome c, suggesting a different mode of cell death, linked to the loss of membrane integrity. Additionally, increased mitochondrial Bim and Bak levels, and a slight release of cytochrome c in untreated HD cybrids may help to explain their moderate susceptibility to mitochondrial-dependent apoptosis